Prevalence and factors associated with stunting and excess weight in children aged 0-5 years from the Brazilian semi-arid region - Clariana V. Ramos; Samuel C. Dumith; Juraci A. César (Elsevier, 2015)
Objective: To analyze the prevalence of excess weight and low height, and identify associated factors among children younger than five years. Methods: Cross-census study. A total of 1,640 children from two municipalities in Piauí, Brazil were included. Results: The prevalence of low height was 10.9% (95% CI: 9.3 to 12.4), inversely associated with mother's younger age and low level of education, lower socioeconomic status, mothers who had fewer than six prenatal consultations, and households that had more than one child younger than 5 years. Excess weight prevalence was 19.1% (95% CI: 17.2 to 21.0), and remained inversely associated with lower maternal age, low maternal education, and cesarean delivery. Stunting was greater in children aged between 12 and 23 months, while excess weight decreased with age. Conclusions: It is noteworthy that the stunting rate, although decreasing, is still high, while the prevalence of excess weight, even in this very poor area, already exceeds the expected percentage for a population with better socioeconomic level. Resumo: Objetivo: Analisar a prevalência de excesso de peso e déficit de altura e identificar fatores associados entre menores de cinco anos. Métodos: Estudo censitário transversal. Foram incluídas 1.640 crianças de dois municípios do Piauí, Brasil. Resultados: A prevalência de déficit de altura foi 10,9% (IC95%: 9,3-12,4), inversamente associado com menor idade e escolaridade materna, menor condição socioeconômica, as mães que realizaram menos de 6 consultas pré-natal e se nessas casas haviam mais de uma criança menor de cinco anos. O excesso de peso teve prevalência de 19,1% (IC95%: 17,2-21,0), e manteve-se inversamente associado com menor idade da mãe, baixa escolaridade materna e parto cesáreo. O déficit de altura foi maior para crianças entre 12 e 23 meses, enquanto o excesso de peso diminuiu com a idade. Conclusões: Destaca-se que o déficit de altura, embora esteja diminuindo, ainda é elevado, enquanto a prevalência de excesso de peso, mesmo nesta área muito pobre, já supera o percentual esperado para uma população com melhores condições socioeconômicas. Keywords: Child, Body weights and measures, Height, Anthropometry, Prevalence, Nutritional transition, Palavras-chave: Criança, Peso e medidas corporais, Estatura, Antropometria, Prevalência, Transição nutricional